INTEGRASI MEDIA BERBASIS PENDEKATAN CONTEXTUAL TEACHING AND LEARNING (CTL) DAN PENDEKATAN DEEP LEARNING DALAM PEMBELAJARAN MATEMATIKA DI SEKOLAH DASAR - Nur Fadilla Nurdin; Felly Herlina Dewi Safitry; Muhammad Edwin; Hamda; Sahrul Syawal (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Mathematics learning in elementary schools continues to face significant challenges, particularly regarding students' low conceptual understanding and learning motivation. This study aims to examine the integration of instructional media based on the Contextual Teaching and Learning (CTL) approach and the deep learning approach in elementary school mathematics instruction. A Systematic literature review (SLR) method was employed by analyzing 15 scientific articles retrieved from Google Scholar and SINTA databases covering the period 2021–2026. The articles analyzed comprised five articles on mathematics instructional media, five articles on the CTL approach, and five articles on the deep learning approach. The findings revealed that: (1) the use of innovative instructional media demonstrably enhances students' interest, engagement, and conceptual understanding in mathematics; (2) the CTL approach effectively connects abstract mathematical concepts to real-life experiences, thereby improving learning outcomes and student engagement; and (3) the deep learning approach fosters students' critical, reflective, and collaborative thinking skills. The integration of these three components holds significant potential to create more meaningful, contextual, and deeper mathematics learning that meets the demands of 21st-century competencies. This study recommends the implementation of an integrated learning model that combines innovative media, the CTL approach, and deep learning principles in elementary school mathematics instruction.